Post 2015: why is the water-energy-land nexus important for the future development agenda? - Clara Brandi; Carmen Richerzhagen; Katharina M.K. Stepping (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
The concept of sustainable development and the idea of an integrated approach that satisfies the complex linkages between water, energy and land should be part of a post-2015 development agenda. Water, energy and land are essential for many lifesupporting functions and key for satisfying basic human needs and development. Access to these resources and their sustainable management are the basis for sustainable development. Sector policies regarding water, energy and land are intertwined, particularly in their trade-offs. Policies for one sector often entail consequences – externalities – for the other two sectors, be they on a local, national, regional or global scale. These interconnections add to current pressures on water and land as well as on resources that fuel our energy system, and will thus exacerbate existing scarcity problems, as the demand for food, water and energy is expected to rise by 30–40 per cent by 2030. In the outcome document of Rio+20, water, energy and land feature as priority areas for the formulation of Sustainable Development Goals (SDGs). As regards water, SDGs should build on existing concepts like Integrated Water Resource Management (IWRM) and the human right to water. The UN Secretary General's Sustainable Energy for All (SE4ALL) initiative illustrates what SDGs could look like for the energy sector. SDGs related to land and biodiversity could build on the UN Convention to Combat Desertification (UNCCD) initiative, which aims at reducing the rate of land degradation, and on the new biodiversity targets that were negotiated in 2010 under the Convention on Biological Diversity (CBD). In order to take account of the nexus between water, energy and land, any proposed list of goals for a post-2015 agenda needs to meet three requirements: Balancing the social, economic and environmental dimension: the goals should integrate and balance social, economic and environmental dimensions of sustainability to promote synergies and avoid tradeoffs among them. Achieving coherence across goals: the goals should be coherent with other (sustainable) development goals of the post-2015 agenda and take into account an integrated perspective with a view to the waterenergy- land nexus. Agreeing on universal goals: the goals should apply to all countries universally rather than only to developing countries. In general, new goals should take into account secondorder conditions related to other dimensions (e.g. in the context of sustainable development or the water-energyland nexus), different levels (global, regional, national etc.) and be adapted to countries' diverse states of development (high-income, middle-income, low-income).
Keywords: 330; Armut und Ungleichheit; Energie; Landwirtschaft und ländliche Entwicklung; Umwelt; Ökosysteme und Ressourcen; Wasser